Biosynthesis of zinc oxide nanoparticles using extracts of Moringa Oleifera: Structural & optical properties. (2021) - Ngom, I.; Ngom, B.D.; Sackey, J.; Khamlich, S.
Abstract: This contribution reports on the biosynthesis of Nanoscaled Zinc oxide nanoparticles (ZnO-NPs) using natural extracts from various parts of the Moringa Oleifera as effective chelating agents. More precisely, natural extracts from flowers, seeds and leaves of Moringa Oleifera as chelating and/or oxidizing/reducing agents of zinc nitrate hexahydrate are reported for the first time in the current literature. The structural and optical properties of ZnO-NPs obtained by the leaves are slightly different from those obtained with the other extracts. The average crystallite sizes of ZnO-NPs calculated via X-rays diffraction analysis are found to be 13.2, 13.9, and 10.8 nm for ZnO-NPs synthesized by the flowers, seeds, and leaves respectively while the direct band gap values deducted from Tauc approximation are 3.12, 3.18 and 3.25 eV. From the photoluminescence analysis at room temperature, a broad band in the visible centered around 450 nm is obtained for all the zinc oxide nanoparticles. One major bioactive compound for each solution extract was used to propose a mechanism of the reaction of ZnO-NPs formation: L-ascorbic acid for the leaves, quercetin for the flowers and oleic acid for the seeds.